Risk factors of health workers with COVID-19 in a hospital in Lima-Este, 2020 - Chávez Sosa, Janett (2021)
Objective: To determine the risk factors of health workers with COVID-19 in a Hospital in Lima-Este.Methodology: Retrospective cross-sectional study of cases and controls, which considered healthworkers with COVID-19 as cases and those without infection as controls, having a total sample of84 workers (28 cases and 56 controls). The risk factors that were considered were: anthropometricmeasurements (BMI and abdominal circumference), risk of suffering from Diabetes Mellitus (FindriskTest) and Peripheral Arterial Disease (ankle / arm index). For data analysis, the statistical packageSPSS v.24 was used. For the univariate analysis, simple frequency tables were used and contingencytables with chi-square test for the bivariate. Finally, the association measure Odds Ratio (OR) wasused. Results: 69% of the health workers were female and 31% male, with an average age of 44.2± 9.6 years. The variable BMI (OR = 67,5; IC 95% = 8,44 – 53,94) and abdominal circumference (OR= 6,67; IC 95% = 1,43-31,1) were associated with a higher risk to present COVID-19. However, nothaving the risk of suffering from Diabetes Mellitus (OR = 0,19; IC 95% = 0,06-0,53). It works as a protective factor to avoid presenting COVID-19. Conclusion: A BMI and abdominal circumferenceincreased the risk of presenting COVID-19 in health workers. On the other hand, not having a risk ofsuffering from Diabetes Mellitus is a protective factor for not presenting COVID-19.